Electrical properties of LaxSr1-xTiO3-δ as SOFC electrode material - Sharma U.; Jha P.A.; Jha P.K.; Singh P. (My University, 2025)
Lanthanum Strontium Titanate Oxide LaxSr1-xTiO3-δ (x = 0.5) with perovskite structure is one of the promising materials to work as an excellent anode in intermediate temperature solid oxide fuel cells (IT-SOFCs). In the present work, the composition with × = 0.5 was synthesized via solid state reaction route (SSR). The X-ray diffractograms revealed that it is crystallized in cubic (Pm 3¯ m) structure and is in accordance with the reported results. Electrical properties are studied in the frequency range 1 Hz to 1 MHz and temperature RT to 700 °C. The I-V characteristics showed the increase in leakage current at room temperature in LaxSr1-xTiO3-δ.Thermogravimetric analysis has been performed to estimate oxygen content. Further, oxygen reduction reaction has also been studied using cyclic voltammetry with the variation of scan rate. © 2022